Fashion Concept as Culturally Projected Within Ghana’s Most Beautiful (GMB) Beauty Pageant in Ghana - Scholastica Wompakeah Azuah; Eric Asante Appau (Fashion and Textiles Review)
The orientation toward continuous change can be found in the modern society through beauty pageants. Fashion is one of the most visible media of change which is reflected in aesthetics, politics, economics, cultural and social life. The Ghana’s Most Beautiful pageant has as its objective, redefining beauty and projecting Ghanaian cultural values to unite the country. Varied opinions of the general public continue to pour out every year regarding pageants which sometimes result in disagreements on the weekly evictions and final crowning of the overall winner of GMB. Fashion is one of the main tools engaged in beauty pageantry to achieve objectives. However, the contribution of fashion within the GMB pageant has not been clearly defined. The purpose of this paper is to illustrate the role played by fashion in beauty pageants such as GMB and the vital contributions made. The research is qualitative with Ghanaian TV3 pageant stakeholders forming the population. It was revealed that fashion played a major role in beauty pageants and has the tendency to change lives through its activities. It is recommended that the fashion concept should be studied carefully to ensure it does not go against the main objectives of the pageant.